UPACARA PEWINTENAN JRO PASEK DESA PAKRAMAN LES-PENUKTUKAN: KAJIAN LINGUISTIK BUDAYA - I Ketut Riana; Putu Evi Wahyu Citra Wati; Fransiska Dewi Setyowati (Program Magister Linguistik Universitas Udayana, 2019)
Mewinten or Upanaya is one of the Manusa Yadnya ceremonies. Physically, mewinten berate is a self purification conducted by using water and flowers. Jro Pasek’s pewintenan ceremony at Pakraman Village Les-Penuktukan is one of the Bali Aga or Bali Kuna society’s ceremonies. It aims to purify the personal to be headmen of the ritual ceremony. In custom, he has the duty to lead the ceremony and society. Initially, the ceremony is purified at the personal selected of Jro Pasek’s house. And then, during the afternoon the selected Jro Pasek enter Bale Agung temple accompanied by the village custom to conduct pewintenan ceremony. This ceremony leads by the eldest and highest position as Jro Mangku at Les-Penuktukan, Jro Mangku Puseh. Moreover, Jro Pasek will be staying up late (mekemit) at the temple for 3 days. After 3 days it will be continued with mancangkarma ceremony to the beach. This study is a field research assisted with some techniques to collect datas such as: interview and note taking. All recorded data then being transcript by data cards. Formal and informal methods are the techniques used for the discussion of result analysis. Formal method consists of with symbols, table, etc., meanwhile informal method is using words in explanation.